Impact of Social Media Marketing on Brand Equity of Small & Medium-sized Enterprises (SMEs) in UAE - Ali, Khulood (European Journal of Business and Strategic Management, 2023)
Purpose: To investigate the impacts of SMM on brands equity of SMEs in UAE. Methodology: We administered a survey using SurveyMonkey.com to select 50 participants, with a developed questionnaire emphasizing the effects of SMM on brand awareness, brand loyalty, brand image, customer engagement, and brand equity. Findings: Findings indicated that social media marketing (SMM) of SME brands in the UAE affect their brand equity, brand image and brand awareness. However, there was no sufficient evidence supporting the effect of SMM of SMEs in the UAE on brand loyalty and customer engagement. This implies that social media marketing activities of firms alone may not be enough to influence loyalty among customers towards the brand. Unique Contribution to Theory, Practice and Policy: The study assists business owners of SMEs in the UAE in evaluating the worthiness of investing in SMM to grow their customer base and maintain strong brand equity.